Strategi Tim Visual Indozone.Id Dalam Perancangan Infografik Di Media Sosial Instagram (Jurnal Kajian Media, 2021)
This study aims to see how the strategy of the indozone.id visual team in designing infographics on Instagram social media. The research statement proposed is how the strategy of the indozone.id visual team in designing infographics on Instagram social media? In this study using a qualitative descriptive method based on the constructivist paradigm. The research subjects were the Visual Team, Editors, and Followers of the indozone Instagram account. With the data collection techniques of observation, interviews and documentation conducted through key-information and informants, this study uses the Media Ecology theory from MC. Luhan. In its implementation, online media owners produce various elements in the news they make. Online news agencies are always prone to convey unverified information to the wider community which results in misperception and misinterpretation of news that has facts. Therefore the focus of this research is the strategy of the indozone.id visual team in designing infographics on social media Instagram. The results of this study can be seen that the strategies implemented by indozone.id include making infographics easy to understand, interesting titles, looking for news to be used as infographics, obstacles when making infographics. This strategy was carried out by the visual team in presenting the infographic. Keywords: Strategy, Online Media, Infographics, Instagram